2021
DOI: 10.1109/access.2021.3071457
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Tracking Active Disturbance Rejection Control of the Unmanned Helicopter and Its Parameters Tuning

Abstract: To solve the problem that the trajectory tracking control system of the unmanned helicopter is limited by the accuracy of the physical model (parameters and dynamic characteristics) and external disturbance of the unmanned helicopter, this paper designs a trajectory tracking control system of the unmanned helicopter based on the linear/nonlinear hybrid Active Disturbance Rejection Control (ADRC). At the same time, this paper proposes a method for tuning the controller parameters based on the Bacterial Foraging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Huang et al applied the double-chains quantum genetic algorithm to optimize the parameters of ADRC [25]. A bacterial foraging optimization-flower pollination algorithm (BFO-FPA) was developed by Shen et al for tuning ADRC parameters [26]. All the above optimization algorithms have good application simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al applied the double-chains quantum genetic algorithm to optimize the parameters of ADRC [25]. A bacterial foraging optimization-flower pollination algorithm (BFO-FPA) was developed by Shen et al for tuning ADRC parameters [26]. All the above optimization algorithms have good application simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation and flight tests showed that the ADRC could effectively estimate and overcome the influence of the total disturbance of a tilt-rotor UAV. However, the state error nonlinear control law (SENCL) in the ADRC controller had a weak dynamic performance and poor rapidity [28]. The backstepping control had better dynamics and rapidity, which could compensate for the defects of SENCL [29,30].…”
Section: Introductionmentioning
confidence: 99%